تعثر ديون الأسر وكيفية علاجه دراسة فقهية تحليلية لتطبيقات البنوك الإسلامية بماليزيا - عمري، محمد الشريف (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2017)
The research discussed Household default debts and its treatments from a jurisprudential approach with the focus on the Islamic banks practices in Malaysia. It discusses the imposition of penalties, compensation, rescheduling and restructuring of the household default debts and their jurisprudence legitimacy. In addition, the study investigates resolving household default debts through judiciary the alternative disputes resolution such as reconciliation and arbitration and their applications via courts, Credit Counseling and Debt Management Agency (CCDM) and Kuala Lumpur Regional Centre for Arbitration (KLRCA). In order to investigate these themes, the study has adopted various research methods, namely the inductive, analytical, and comparative approaches. It is a library research with a little field study using questionnaires distributed to Islamic banks in Malaysia along with interviews conducted with the heads of Sharia'h departments, divisions of debt recovery, Islamic banks chief executive officers, some renowned scholars in the Islamic banking industry, and executive officers from the Zakat institution and Baitulmal. This study concluded with a set of results, most importantly; the need to review the compensation amount imposed on default debtors, as it does not represent the actual loss suffered by the bank; the necessity to find standards by the supervisory authorities to determine the actual loss; the researcher's concurrence with those who allow the imposition of penalty, intended to be distributed to charities, as a temporary solution to deter procrastinators; the necessity to review debt restructuring models applied in Islamic banks, especially the roll-over debt applied by those banks; and coming up with more forms accepted by the Shariah rules. Furthermore, the researcher urges to establish an Islamic judicial system that punishes procrastinators by means of criminal law rather than financial penalties. The study is finalized by suggesting two models to resolve household default debts. The first is based on entitling destressed debtors to Zakat under the category of persons in debt, and the other suggestion is by establishing a cooperative fund between the government and the central bank with the contribution of Islamic banks in solving the cases of distressed clients in those banks.